INTER-SUBJECT INTERACTION IN COLLECTIVE GAME ACTIVITY - Nakonechna, Maria (PSYCHOLOGICAL JOURNAL, 2018)
Theoretical analysis of intersubject cooperation problem and results undertaken from pilotage experimental study are presented in the article. The analysed idea of the article says that for the sake of intersubject cooperation is quite important what takes place between people, being diffused between them; what can not take place, if people do not co-operate. It is underlined that real intersubject cooperation assumes increased personality’s inner complexity, openness of a person to new challenges invoked by communication and dialogue. Conceptual vision of psychological phenomenon of intersubjectness is focused on three correlated aspects: 1) intersubject diffuseness into space of subject wills; 2) reciprocity aspect (“I am a subject in relation to you and I am expecting you to be a mutual subject”); 3) developmental aspect: a function is intersubjective at first, diffused between people, but then it becomes intra-subjective, turning into an achievement of my own development (according to L.S. Vygotsky’s methodology). It was proven that intersubject cooperation involves such communication that exposes subject qualities of a person during communication process, resulting in personal development. Modified checkers game was chosen as experimental model. After a “classic” game session respondents were asked to play otherwise in order that the minimum of checkers should remain on a game board. Following hypotheses were tested: 1) intersubject cooperation is a special form of organization of diffused activity, that is characterized by the only aim and predominance of collaboration strategy; 2) involvement into intersubject cooperation (as exemplified by “intersubject checkers”) increases human satisfaction rates. After every game session in both classic and intersubject settings respondents were asked to estimate their satisfaction level using scale from 1 to 10, where 10 stands for the most satisfactory option. On most parameters subjectively estimated level of satisfaction is higher after intersubject checkers sessions. These data are confirmed by visual observation over players during different sessions. Research hypotheses were confirmed. Consequently, initial ideas about intersubject cooperation as complex process of mutual development of subject qualities among human participants were further extended.